Pengelolaan Pawon Luwak Coffe Borobudur Berbasis Wisata Edukasi - Amelia, Viona; Prasetyo, Danang (Metta : Jurnal Ilmu Multidisiplin, 2023)
Tourism has great potential to provide economic benefits to society, but can also cause environmental and social damage if not managed properly. Overcoming this requires implementing the concept of sustainable tourism. That is what Pawon Luwak Coffee Borobudur has done as an educational tourism-based coffee shop. Its existence has served as an example of an industry that provides coffee and shares knowledge by directly inviting people to see the process of making it. This research uses a descriptive method with a qualitative approach to explore in depth the process of managing a coffee shop based on educational tourism that has been implemented. The results and discussion in this research found that the educational tourism-based coffee shop management process has been implemented. Through detailed explanations by employees, they also act as tour guides to invite visitors to experience and gain knowledge about the process of making drinkable Luwak coffee. The management of the Pawon Luwak Coffee coffee shop based on educational tourism has the advantage of providing high quality Luwak coffee and providing a unique experience for visitors to see the process firsthand. Then the development of attractive educational programs requires improvements, such as collaborating with local communities in terms of production, environmentally friendly operations, employee skills development training, as well as evaluating sustainable practices that can be adopted. Managing a Luwak coffee shop based on sustainable educational tourism can provide economic benefits, promote environmental awareness, social networking, and become a positive example for the coffee industry as an alternative tourism in Indonesia. Based on the three pillars of sustainability, namely environmental, social and economic, it can be concluded that this coffee shop has become a positive example for the coffee industry as part of tourism in Indonesia.